Exposure to Early Life Stress Results in Epigenetic Changes in Neurotrophic Factor Gene Expression in a Parkinsonian Rat Model - Thabisile Mpofana; Willie M. U. Daniels; Musa V. Mabandla (Parkinson's Disease)
Early life adversity increases the risk of mental disorders later in life. Chronic early life stress may alter neurotrophic factor gene expression including those for brain derived neurotrophic factor (BDNF) and glial cell derived neurotrophic factor (GDNF) that are important in neuronal growth, survival, and maintenance. Maternal separation was used in this study to model early life stress. Following unilateral injection of a mild dose of 6-hydroxydopamine (6-OHDA), we measured corticosterone (CORT) in the blood and striatum of stressed and nonstressed rats; we also measured DNA methylation and BDNF and GDNF gene expression in the striatum using real time PCR. In the presence of stress, we found that there was increased corticosterone concentration in both blood and striatal tissue. Further to this, we found higher DNA methylation and decreased neurotrophic factor gene expression. 6-OHDA lesion increased neurotrophic factor gene expression in both stressed and nonstressed rats but this increase was higher in the nonstressed rats. Our results suggest that exposure to early postnatal stress increases corticosterone concentration which leads to increased DNA methylation. This effect results in decreased BDNF and GDNF gene expression in the striatum leading to decreased protection against subsequent insults later in life.